2020
DOI: 10.3390/foods9050597
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive and Bioactive Properties of Mesquite (Prosopis pallida) Flour and Its Technological Performance in Breadmaking

Abstract: Although the nutritional profile, bioactivities, and uses of mesquite pod flour from various Prosopis species have been studied, limited research has been conducted on Prosopis pallida (Humb, & Bonpl. Ex Willd.) Kunth mesquite flour. This study aimed to characterize the nutritional quality and bioactive properties of P. pallida pod flour and to assess its technological performance in breadmaking as a partial replacer of white wheat flour. Peruvian P. pallida mesquite flour was found to have an appealing nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…Regarding fat, the higher the mesquite amount the lower the fat content, with 10 and 15% enriched bread showing significantly lower amounts. This was expected as the fat content of Peruvian mesquite flour is low (1.0 ± 0.1 g/100 g dw), as reported in our previous study (Gonzales-Barron et al, 2020).…”
Section: Macronutrient Quality Of Wheat-mesquite Flour Composite Breadsupporting
confidence: 83%
See 3 more Smart Citations
“…Regarding fat, the higher the mesquite amount the lower the fat content, with 10 and 15% enriched bread showing significantly lower amounts. This was expected as the fat content of Peruvian mesquite flour is low (1.0 ± 0.1 g/100 g dw), as reported in our previous study (Gonzales-Barron et al, 2020).…”
Section: Macronutrient Quality Of Wheat-mesquite Flour Composite Breadsupporting
confidence: 83%
“…A full two-factor design was employed, varying the replacement of wheat flour of either type 55 or 65 with mesquite flour (0, 5, 10 and 15% w/w), which produced a total of 8 treatments repeated twice. Previous research showed that up to a substitution level of 10%, the addition of Peruvian mesquite flour significantly increases loaf volume and produces a more uniform crumb aspect consisting of more alveoli of small size (Gonzales- Barron et al, 2020). For that reason, replacement levels higher than 15% were not tested in the present study.…”
Section: Materials For Bread-making and Experimental Designmentioning
confidence: 92%
See 2 more Smart Citations
“…Además de su aporte nutricional debe destacarse el alto contenido de fibra dietética (principalmente fibra insoluble), así como su composición aminoacídica de las proteínas deja ver la presencia de importantes cantidades de aminoácidos esenciales, excepto (según la especie) de metionina, isoleucina y treonina(Ortiz 2019). Por otro lado, en el estudio realizado en árboles de P. laevigata, ubicados en la Cañada Oaxaqueña, específicamente en Teotitlán de Flores Magón, Oaxaca, se encontró que las vainas presentaron un alto contenido de humedad, grasa, ceniza y carbohidratos, al compararlo con los resultados para otros Prosopis descritosProkopiuk 2004;Barba de la Rosa et al, 2006; Ruiz, 2011;González-Barrón et al, 2020). No obstante, cabe señalar que los valores obtenidos en este estudio, presentan diferencias; lo anterior debido a las variedades de Prosopis, al estado de madurez de la vaina (vaina verde, vaina madura y vaina seca), el tratamiento aplicado a la vaina previo al secado, así como la fracción de la vaina (mesocarpio, endocarpio, pericarpio y semilla) utilizada para el estudio.Mesocarpio Endocarpio Semilla…”
unclassified